Circulating neutrophils activated by cancer cells and M2 macrophages promote gastric cancer progression during PD-1 antibody-based immunotherapy - Zhou, Chenfei; Guo, Liting; Cai, Qu; Xi, Wenqi; Yuan, Fei; Zhang, Huan; Yan, Chao; Huang, Lei; Zhu, Zhenggang; Zhang, Jun (Frontiers in Molecular Biosciences, 2023)
Aims: To analyze the correlation between the neutrophil-to-lymphocyte ratio (NLR) and prognosis of advanced gastric cancer (AGC) patients treated by PD-1 antibody-based therapy and to delineate molecular characteristics of circulating neutrophils by single-cell RNA sequencing (scRNA-seq). Methods: The clinicopathological information of 45 AGC patients receiving PD-1 antibody-based regimens at the Department of Oncology, Ruijin Hospital, was reviewed. Treatment outcomes including objective response rate (ORR), progression-free survival (PFS), and overall survival (OS) were recorded. The correlation between NLR and efficacy of PD-1 antibody-based treatment was analyzed. Single-cell RNA sequencing (scRNA-seq) analysis was performed based on multisite biopsy samples from two AGC patients to explore the molecular characteristics of circulating neutrophils and their pro-tumor mechanisms. Tissue samples from 88 gastric cancer patients who underwent radial gastrectomy were collected for immunochemistry staining. Results: A high posttreatment NLR was associated with poor outcomes of AGC patients receiving PD-1 antibody-based regimens. scRNA-seq analysis showed that an increased number of circulating neutrophils were found in peripheral blood samples after treatment in which neutrophil cluster 1 (NE-1) was the major subcluster. NE-1 was featured with a neutrophil activation phenotype with the high expression of MMP9, S100A8, S100A9, PORK2, and TGF-β1. NE-1 displayed an intermediate state in pseudotime trajectory analysis with gene function enrichment found in neutrophil activation, leukocyte chemotaxis, and negative regulation of MAP kinase activity. Cellular interaction analysis showed that the chemokine signaling pathway is the major interactional pathway of NE-1 between subclusters of malignant epithelial cells (EP-4) and M2 macrophages (M2-1 and M2-2). In turn, the MAPK signaling pathway and Jak-STAT signaling pathway of EP-4, including IL1B/IL1RAP, OSM/OSMR, and TGFB1/TGFBR2 axes, were identified as interacting pathways between EP-4 and NE-1. The high expression of OSMR in tumor cells was closely correlated with lymph node metastasis of gastric cancer. Conclusion: The posttreatment NLR could be a poor prognostic marker of AGC patients treated with immune checkpoint inhibitors (ICIs). Subclusters of circulating neutrophils activated by tumor cells and M2 macrophages could participate in gastric cancer progression through signaling interactions with tumor cells.